COVID-19 and cancer: A comparative case series. (2021) - Mousavi, Seied Asadollah; Rostami, Tahereh; Kiumarsi, Azadeh; Rad, Soroush; Rostami, Mohammadreza; Motamedi, Fatemeh; Gandomi-Mohammadabadi, Alireza; Mirhosseini, Amirhossein
Highlights: Mortality rate among cancer patients affected by COVID-19 is higher than general population. Mortality has a significant correlation with the stage, type and activity of cancer. Sepsis, invasive ventilation and mortality is significantly higher in patients who receive cytotoxic chemotherapy within the last 14 days. Outcome of cancer patients with positive RT-PCR for COVID-19 is similar to those with negative RT-PCR with highly suggestive chest CT scan findings. Abstract: Background: Cancer patients, with an incidence of more than 18 million new cases per year, may constitute a significant portion of the COVID-19 infected population. In the pandemic situation, these patients are considered highly vulnerable to infectious complications due to their immunocompromised state. Material & Methods: In this retrospective case series, the documents of solid cancer patients infected by SARS-CoV-2, hospitalized in Shariati hospital between 20 February and 20 April 2020, were evaluated. The diagnosis of COVID-19 was based on laboratory-confirmed COVID-19 and/or features of chest CT scan highly suggestive for SARS-CoV-2. Results: A total of 33 COVID-19-infected cancer patients were included. Mean age was 63.9 years, and 54.5% of the patients were male. LDH level was significantly higher (1487.5 ± 1392.8 vs. 932.3 ± 324.7 U/L, P-value=0.016) and also serum albumin was significantly lower in non-survivors (3.6 ± 0.5 vs. 2.9 ± 0.6 g/dL, p-value=0.03). Among 16 patients with stage IV cancer, thirteen patients died, which was significantly higher compared to stage I-III cancer patients (81.3% vs. 18.8% P-value= <0.001). In terms of developing complications, sepsis, invasive ventilation and mortality was significantly higher in patients who received cytotoxic chemotherapy within the last 14 days. Conclusion: In this study, we showed that the mortality rate among cancer patients affected by COVID-19 was higher than general population and this rate has a significant correlation with factors including the stage of the disease, the type of cancer, the activity of cancer and finally receiving cytotoxic chemotherapy within 14 days before diagnosis of COVID-19.